POTENSI DAYA TARIK WISATA ALAM RIAM SUNGAI MANAH DI DESA SUNGAI MUNTIK KECAMATAN KAPUAS KABUPATEN SANGGAU - Purnama, .; Siahaan, Sarma; Widiastuti, Tri (Universitas Tanjungpura, 2018)
Sungai Muntik is an area in Kapuas Sub district, Sanggau Regency, West Kalimantan Province. According to Decree number 5389/Menhut/VII/KUH/2014 about the appointment of forest area in Kalimantan Island, it is stated that Manah River Cascade is located in the area of limited production forest (HPT) of Tinjil Mountain in Sungai Buayan, Sanggau Regency. This research aims at identifying the potential of tourist attraction at Manah River Cascade in Sungai Muntik. Data gathered for this research involved tourist attraction, accessibility, socio-economic condition, accommodation, infrastructures and facilities, and the availability of clean water. This all was conducted to follow the guidelines of tourist attraction analysis, so-called ODTWA (2003). It was analyzed by using a scoring method and formulation of S = NxB. The data was gathered through questionnaires and direct observations. Based on the data analysis, the total score of each criteria was 3384.72 which meant good â€œBâ€ to be developed as a tourist object in Manah River Cascade.Keywords: Fauna, Flora, Manah River, Natural Tourist Attraction